Targeted next-generation sequencing of a cancer transcriptome enhances detection of sequence variants and novel fusion transcripts - Levin, Joshua Z; Berger, Michael F; Adiconis, Xian; Rogov, Peter; Melnikov, Alexandre; Fennell, Timothy; Nusbaum, Chad; Garraway, Levi A; Gnirke, Andreas (Genome biology, 2009)
Targeted RNA-Seq combines next-generation sequencing with capture of sequences from a relevant subset of a transcriptome. When testing by capturing sequences from a tumor cDNA library by hybridization to oligonucleotide probes specific for 467 cancer-related genes, this method showed high selectivity, improved mutation detection enabling discovery of novel chimeric transcripts, and provided RNA expression data. Thus, targeted RNA-Seq produces an enhanced view of the molecular state of a set of "high interest" genes.